Upaya meningkatkan minat belajar siswa melalui penggunaan aplikasi Educandy dalam pembelajaran Sejarah (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Interest in learning is one of the important factors that influence student learning so that learning becomes optimal. The indicators in this research consisted of student involvement, student interest, student attention, and student feelings of pleasure. This research used classroom action research method and was carried out in 2 cycles. The design of this research used Kemmis and McTaggart model whose stages consist of planning, acting, observing, and reflecting on each cycle. Data collection techniques in this research are by means of observation, interviews, and documentation studies. The results of this research indicate that after using the Educandy application in history learning, students’ interest in learning can increase significantly. The increase in student interest in learning can be seen from the acquisition of the sub-indicator assessment of student interest in learning after using the Educandy application in history learning. From the results of this research it can be concluded that the use of the Educandy application in history learning can be an alternative to increase student interest in learning in class XI IPS 3 SMA Kartika XIX-1 Bandung.
Keywords: Aplikasi; Educandy; minat belajar; pembelajaran sejarah